(NsO^INENIQ DLQ fORTEPIANO (BIIIs (NnOTYs - (Nf(B. (NlISTs ((NmOSKWAs (NmUZYKAs, 1966)
(Nw NASTOQ]IJ TOM WO[LI NEBOLX[IE (B( (NILI SRAWNITELXNO NEBOLX[IE(B) (NORIGINALXNYE FORTEPIANNYE SO^INENIQ(B.s
Keywords: (NFORTEPIANOs